일부 종합병원 임상병리사의 계속교육 긍정도와 그에 미치는 요인분석 - 여영규 (연세대학교 보건대학원, 1989)
[한글] 임상병리사의 계소교육 긍정도와 그에 미치는 요인을 파악하고자 대한임상병리사협회에 가입된 회원중 서울지역의 일부 종합병원에 근무하는 임상병리사를 대상으로 1988년 8월 1일 부터 8월 10일까지 10일간 300매의 설문지를 배부하여 자기응답식 설문조사방법으로 측정하여 다음과 같은 결과를 얻었다. 1. 계속교육 프로그램에 참여 현황을 살펴보면, 1년에 10평점 이상 이수한 대상자는 82.8%였으며, 주로 협회 주관의 학술대회 및 보수교육, 병원내 세미나의 프로그램에 참여가 높았다. 2. 계속교육을 원하는 분야로는 면역. 혈청학 분야가 25.1%, 임상미생물학 분야가 17.2%, 조직, 세포학 분야가 16.3%, 임상화학 분야가 14.4%의 순으로 응답했다. 3. 계속교육의 형태로는 강의와 시범이 46.5%, 세미나가 27.0%, 그룹토의가 20.5%의 순으로 응답했다. 4. 계속교육에 참여하기 어려운 이유로서는 원하는 주제가 마련되지 않기때문에가 24.7%, 근무시간과 겹치기 때문에가 24.2%, 자신의 노력과 열의 부족으로가 l6.3%, 교육실시에 대한 정보 부족으로가 8.4%의 순으로 응답했다. 5. 계속교육 긍정도와 일반적 특성의 관계에서 최종학력과 직위가 높을수록 보다 긍정적이였으며 통계학적으로 유의한 관계가 있었다 (P<.01). 6. 계속교육 긍정도와 자아성취도는 r=0.272 였고, 직무만족과는 r=0.333으로 정상관의 관계가 있었으며, 직무만족요인중 동료관계, 전문직태도, 자율성이 유의한 관계가 있었고(P<.001), 의사와의 관계도 유의하였다(P<.01). 7. 계속교육 긍정도를 유의하게 설명할 수 있는 변수로는 자율성, 최종학력, 전문직태도의 3가지 변수였으며, 이들 요인으로서 18.9%를 설명할 수 있었다. 이상을 살펴볼때 직무만족요인이 임상병리사의 계속교육 긍정도와 관련된 중요한 변수였다. 계속교육 긍정도를 높여서 보다 효율적인 교육을 수행하기 위해서는 직무만족도를 높여 주어야겠다. 그리고 임상병리사의 전문적 지식 및 기술을 유지. 신장시키기 위해서는 보다 체계적이고 효율적인 프로그램이 계획되어 제공되어야겠으며, 계속교육 긍정도에 미치는 다른 요인들에 대한 계속적인 연구가 필요하다. [영문] Continuing education is an ever increasing need for medical technologists who want to maintain and upgrade their professional knowledge and skills. In an attempt to measure the factors that affect degree of affirmation for continuing education for medical technologists, a survey was taken on medical technologists using self-administered questionaires in several hospitals in Seoul. These questionaires were distributed to 300 persons from August 1 to August 10, 1988. The return was 226(75.3%). The method of data analysis applied were %, F-test, coefficient of correlation and multiple stepwise regression. The findings of this study were as follows: 1. The most frequently attended programs of continuing education were found to be symposiums, workshops and laboratory seminars. Among the medical technologists who took part in continuing education, 82.8% were awarded 10 or more credits for a year through these programs. 2. The topics of interest for continuing education were immuno-serology(25.1%), microbiology(17.2%), histo-cytology(16.3%) and clinical chemistry(14.4%), etc. 3. The preferred formats of continuing education were lecture and demonstration(46.5%), seminar (27.0%) and group discussion (20.5%), etc. 4. The factors hindering participation in continuing education programs were subject not of interest (24.7%), not granted release time(24.2%), lack of individual effort(16.3%) and not informed in time (8.4%), etc. 5. As to the relationship between the degree of affirmation for continuing education and the demographic factors, the following variables were statistically significant: level of education and job position(P<0.01). 6. In considering the relationship between the degree of affirmation for continuing education and job satisfaction and self-esteem, the following variables were statistically significant: self-esteem (r=0.272), job satisfaction(r=0.333) : coworker, professional attitude and autonomy (P<0.001). 7. The main factors affecting the degree of affirmation for continuing education were the following three variables:autonomy, level of education and professional attitude. These variables explained 18.9% of the total variation. These results suggest that job satisfaction is important factor affecting the degree of affirmation for continuing education of medical technologiats. It is necessary to elevate the job satisfaction, so as to increase the degree of affirmation for continuing education. To increase and maintain continued competence, professional knowledge and skills, more systematic and efficient programs are needed. And further study is needed to find other factors affecting continuing education.
보건학과/석사